Extensive Dissection at No. 12 Station During D2 Lymphadenectomy Improves Survival for Advanced Lower-Third Gastric Cancer: A Retrospective Study From a Single Center in Southern China - Dai, Weigang; Zhai, Er-Tao; Chen, Jianhui; Chen, Zhihui; Zhao, Risheng; Chen, Chuangqi; Yuan, Yujie; Wu, Hui; Cai, Shirong; He, Yulong (Frontiers in Oncology, 2022)
Background D2 lymphadenectomy including No. 12a dissection has been accepted as a standard surgical management of advanced lower-third gastric cancer (GC). The necessity of extensive No. 12 nodes (No. 12a, 12b, and 12p) dissection remains controversial. This study aims to explore its impact on long-term survival for resectable GC. Methods From 2009 to 2016, 353 advanced lower-third GC patients undergoing at least D2 lymphadenectomy during a radical surgery were included, with 179 patients receiving No. 12a, 12b, and 12p dissection as study group. A total of 174 patients with No. 12a dissection were employed as control group. Surgical and long-term outcomes including 90-day complications incidence, therapeutic value index (TVI), 3-year progression-free survival (PFS), and 5-year overall survival (OS) were compared between both groups. Results No. 12 lymph node metastasis was observed in 20 (5.7%) patients, with 10 cases in each group (5.6% vs. 5.7%, p = 0.948). The metastatic rates at No. 12a, 12b, and 12p were 5.7%, 2.2%, and 1.7%, respectively. The incidence of 90-day complications was identical between both groups. Extensive No. 12 dissection was associated with increased TVI at No. 12 station (3.9 vs. 0.6), prolonged 3-year PFS rate (67.0% vs. 55.9%, p = 0.045) and 5-year OS rate (66.2% vs. 54.0%, p = 0.027). The further Cox-regression analysis showed that the 12abp dissection was an independent prognostic factor of improved survival (p = 0.026). Conclusion Adding No. 12b and 12p lymph nodes to D2 lymphadenectomy might be effective in surgical treatment of advanced lower-third GC and improve oncological outcomes compared with No. 12a-based D2 lymphadenectomy.